Tax Uncertainty and Incremental Tax Avoidance - Guenther, David A.; Wilson, Ryan J.; Wu, Kaishu (The Accounting Review, 2019)
ABSTRACT We investigate whether tax avoidance becomes more uncertain as the rate of tax avoidance increases. We estimate a system of equations to demonstrate that as firms' pretax income increases, each additional dollar of potential tax results, on average, in 32.8 cents of tax avoided, which we refer to as incremental tax avoidance. Of the incremental tax avoided, 1.4 cents represent additions to the reserve for uncertain tax benefits (UTB reserve), or 4.3 percent of the total incremental tax avoided. We then partition sample firms into groups that prior research suggests engage in higher rates of tax avoidance, and examine the amount of incremental tax avoidance that results in additions to the UTB reserve. Results demonstrate that the percentage of incremental tax avoidance reflecting additions to UTB reserve is not larger for groups engaging in higher rates of tax avoidance, suggesting higher rates of tax avoidance may not be more uncertain. JEL Classifications: H26; M41; M48.